1996
DOI: 10.1113/jphysiol.1996.sp021147
|View full text |Cite
|
Sign up to set email alerts
|

Changes in IP3 and cytosolic Ca2+ in response to sugars and non‐sugar sweeteners in transduction of sweet taste in the rat.

Abstract: 1. The transduction pathways of sweet-sensitive cells in rat circumvallate (CV) taste buds were investigated with assays for inositol 1,4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(148 citation statements)
references
References 31 publications
13
133
2
Order By: Relevance
“…Using fura-2-loaded taste buds, we verified that, as shown previously (Richter et al, 2004), ϳ50% of taste bud cells are depolarized by bath-applied KCl (50 mM). Also, as shown previously (Bernhardt et al, 1996), cells in isolated taste buds responded to bath-applied bitter tastants (here, 10 -100 M cycloheximide) and saccharin (2-20 mM). Parenthetically, different taste cells responded to cycloheximide, saccharin, or KCl depolarization, but we did not investigate this systematically.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Using fura-2-loaded taste buds, we verified that, as shown previously (Richter et al, 2004), ϳ50% of taste bud cells are depolarized by bath-applied KCl (50 mM). Also, as shown previously (Bernhardt et al, 1996), cells in isolated taste buds responded to bath-applied bitter tastants (here, 10 -100 M cycloheximide) and saccharin (2-20 mM). Parenthetically, different taste cells responded to cycloheximide, saccharin, or KCl depolarization, but we did not investigate this systematically.…”
Section: Resultssupporting
confidence: 73%
“…taste cells via a signaling cascade involving phospholipase C ␤2 (PLC␤2) and IP 3 (Bernhardt et al, 1996;Spielman et al, 1996). Thus, a likely source of Ca 2ϩ for transmitter release elicited by these compounds was an intracellular store.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it has been suggested that animals cannot discriminate compounds that are detected by the same taste cells (Bernhardt et al, 1996;Adler et al, 2000;Dunipace et al, 2001). Our results contradict this suggestion.…”
Section: Functional Implicationscontrasting
confidence: 82%
“…T1R2/3 activates the heterotrimeric G-protein gustducin, which uses cyclic nucleotides and inositol-1, 4, 5-trisphosphate (IP 3 ) as second messengers 20 . Ca 2+ imaging experiments in isolated taste buds of rat vallate, showed that activation of sweet taste receptors with sucrose increased cyclic adenosine monophosphate (cAMP) and Ca 2+ uptake but activation with artificial sweeteners resulted in increased IP 3 and Ca 2+ release 21 .…”
Section: Discussionmentioning
confidence: 99%